O8A.1 Estimating the burden of lung cancer due to occupational exposure to radon gas. (April 2019) - Peters, Cheryl; Kim, Joanne; Song, Chaojie; Ge, Calvin; Demers, Paul
Abstract : Background: Radon is a well-known cause of lung cancer. Our goal was to estimate the prevalence and level of occupational exposure to radon, and to estimate the current lung cancer burden caused by radon exposure in Canadian workplaces. Methods: Highly exposed (i.e. underground) workers were assigned exposure proportions at the national level using CAREX methodology. Exposure for the indoor working population was estimated using province-specific radon measurements from the Canadian federal building survey (n=12 870 samples). The proportion of workers exposed to specific ranges of radon (50–100, 100–150, 150–200, 200–400, 400–800, >800 Bq/m 3 ) were calculated and we assigned the midpoint of the range as the average radon concentration for each exposure group. For the >800 Bq/m 3 category, the province-specific mean of measurements>800 Bq/m 3 was assigned. The above exposure assessment was applied to a population model of the historical Canadian labour force and exposures between 1961 and 2001 (the risk exposure period) were considered as contributing to cancer cases in 2011. The BEIR VI exposure-age-concentration model was used to assign relative risks by exposure category. The population attributable fraction was calculated using Levin's equation. Results: There were an estimated 4.4 million indoor workers and 26 000 highly exposed workers exposed to radon during the risk exposure period. Nearly 80% of these workers were exposed below 50 Bq/m3 (half the WHO reference level). Combining the indoor and highly exposed workers, we calculated that 0.80% of lung cancers are attributable to occupational radon exposure; this equates to 188 lung cancer cases per year. Conclusions: Ours was the first study to use a data-driven approach to estimate radon exposure and lung cancer burden for indoor workers. Some of the attributable cases can be prevented by reducing workers' exposure at workplace.